Penyuluhan Hukum Tentang Dampak Perjanjian Gadai Tanah Terhadap Tingkat Ekonomi Masyarakat Hukum Adat Negeri Piliana Kabupaten Maluku Tengah - Jenny Kristiana Matuankotta; Mahrita Aprilya Lakburlawal; Pieter Radjawane (Faculty of Law, Universitas Pattimura, 2023)
Introduction: This article analyzes the impact of land pawning agreements which tend to be the choice of customary law communities, especially in the Philippines, to obtain funds in a short time, but the implementation of land pawning does not take place without problems, especially if the land pawning agreement is not signed correctly, it will very detrimental to the pawnbroker as the land owner.Purposes of Devotion: Providing knowledge and understanding to the community about the impact of land pawning agreements on the customary law communities of Piliana State, especially so that the land pawning agreements carried out do not harm the pawning party as the land owner. Method of Devotion: Legal counseling is carried out guided by the panel discussion method. Namely, the presenters will present the counseling material in turns, followed by a question and answer session with village officials and the community.Results of the Devotion: The Customary Law Community in Pliana village, which lives at the foot of Mount Binaya, Tehoru District, Central Maluku Regency, is a community group with a lower middle economic level and a low level of education. Therefore, they tend to enter into hamlet land pawning agreements. However, the implementation of pawning based on custom without knowledge of the law regarding pawning causes the people of Piliana State, especially members of the pawnbroker's association's hamlet land owners, to suffer losses because land pawning can last more than seven years or even decades and as long as the rights to the hamlet land are in their hands. pawn recipients, thereby worsening the community's economy.